Versatile, cost-effective and highly-multiplex nucleic acid detection through the Engineered Hairpin Cleavage Amplification (EHCA) strategy - Liu, Zhaocheng; Zhang, Rui; Zhang, Yi; Mu, Huijun; Jiang, Xinyi; Zou, Jian; Wang, Tingting; Yin, Ying (Chemical engineering journal (Lausanne, Switzerland : 1996), 2025)
Real-time quantitative PCR (qPCR), droplet digital PCR (ddPCR), and CRISPR/Cas diagnostics typically rely on expensive, target-specific fluorescence probes or CRISPR RNA (crRNA) for precise nucleic acid detection, and their multiplexing capability is limited by the scarcity of fluorescent colors in fluorometric thermal cyclers. To overcome these limitations, we introduced Engineered Hairpin Cleavage Amplification (EHCA), a novel technique that is compatible with various platforms such as qPCR, ddPCR, CRISPR/Cas12a and melting curve analysis (MCA), utilizing universal fluorescence probes/crRNA. EHCA employs a unique mechanism in which Taq polymerase cleaves engineered hairpins to release secondary primers, thereby extending helper targets or fluorescence probes. EHCA, efficiently developed with the aid of computational tools, exhibited comparable detection sensitivity and precision to specific probe assays. Furthermore, EHCA-MCA demonstrated multiplexed detection capabilities by generating fluorescent double strands of different lengths (Tm) and colors. Detection of nucleic acids with high sensitivity was achieved using EHCA-MCA at annealing temperatures between 46 and 66 °C, highlighting the remarkable temperature-robustness. In evaluating 213 clinical samples for high-risk HPV genotyping, the 14-plex EHCA-MCA yielded a sensitivity of 92.2 %, specificity of 98.1 % and detection accuracy of 96.7 %. With its versatility, cost-effectiveness, simplicity, high sensitivity, and multiplexing capabilities, the EHCA strategy is anticipated to be widely utilized. •Enables universal probe/crRNA-based nucleic acid detection across different platforms, eliminating target-specific reagents.•Investigates the novel mechanism of Taq polymerase-mediated hairpin cleavage and secondary primer extension.•Develops Engineered Hairpin Cleavage Amplification (EHCA) with computationally optimized hairpin design.•Breaks multiplexing barriers in EHCA-MCA by generating fluorescent dsDNA with distinct melting temperatures (Tm) and colors.